A case report of necrotizing fasciitis with a sole causative agent: Actinotignum schaalii: Necrotizing fasciitis due to Actinotignum schaalii - Michalczak, Mateusz; Michalczak, Jakub; Olechowska-Jarząb, Aldona; Rymarowicz, Justyna (Journal of Surgery and Medicine, 2025)
Actinotignum schaalii (A. schaalii) is a Gram-positive, anaerobic bacterium. While primarily associated with urinary tract infections in elderly and immunocompromised individuals, it has also been implicated in soft tissue infections such as necrotizing fasciitis. However, its role as a primary pathogen in necrotizing fasciitis outside the genitourinary region remains underreported. We present a case of necrotizing fasciitis of the axilla caused by A. schaalii in an elderly diabetic female. This case is unique in that it highlights the bacterium’s role as the sole causative agent in a severe soft tissue infection, diverging from its typical polymicrobial involvement. This case emphasizes the pathogenic potential of A. schaalii in severe soft tissue infections and highlights the importance of advanced microbiological techniques for its accurate identification.